Hubungan rasio neutrofil limfosit terhadap derajat klinis kejadian DBD - Asni Ramayana Tina; Reski Ananda Idris; Evi Damayanti; Sanatang Sanatang (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Dengue Hemorrhagic Fever (DHF) is a global health problem caused by dengue virus infection, with the Aedes aegypti mosquito as the primary vector. This disease has a broad clinical spectrum, ranging from mild symptoms to severe complications such as Dengue Shock Syndrome (DSS), which can be fatal. Therefore, simple laboratory parameters are needed to help assess disease severity early. One widely studied hematological biomarker is the neutrophil-lymphocyte ratio (NLR), which represents the systemic inflammatory response. Purpose: To analyze the relationship between the neutrophil-lymphocyte ratio and the clinical severity of dengue hemorrhagic fever. Method: This observational, analytical, and cross-sectional study was conducted from July to August 2025 on 24 patients diagnosed with DHF at Benyamin Guluh Regional General Hospital, Kolaka Regency. The research equipment used included a hematology analyzer, 3cc syringes, tourniquets, hand spoons (PPE), EDTA tubes, and test tube racks. The research materials used were patient blood samples, cotton swabs, 70% alcohol, and plasters. Data collection used secondary data from DHF patient medical records and primary data from blood sample examination results. Data were analyzed using the Chi-Square test. Results: All participants with DHF grades 1 and 2 had normal NLR values, while the majority of participants with grades 3 and 4 had abnormal NLRs (5 participants with grade 3 and 7 participants with grade 4). The Chi-Square test yielded a p-value of 0.001, indicating a significant association between NLR values ​​and DHF severity. Conclusion: There is a significant association between NLR and DHF severity, with the higher the grade, the greater the likelihood of an abnormal NLR. Suggestion: Studies with larger sample sizes and including other variables, such as platelet count, hematocrit, and clinical manifestations, are recommended to provide a more comprehensive understanding of the relationship between NLR and DHF severity. Keywords: Clinical Grade; Dengue Hemorrhagic Fever; Neutrophil-Lymphocyte Ratio.